Face recognition for identify verification in exams locations - Ng, Suet Eng (2023)
This project explores the growing domain of facial recognition technology, known for accurately identifying people based on their unique facial features. This technology has gained popularity across various industries for preventing identity fraud. In the context of exam centres, where confirming candidates' identities is vital, facial recognition can play a crucial role. The main focus of this project is to prevent fraud in exam centres. The system's key requirement is accurately identifying individuals. It also needs to be fast for quick verification. The project uses a mix of hardware and software tools. Hardware includes cameras and laptops, meanwhile software tools include PyCharm Community, OpenCV and the Haar-Cascade Algorithm are used for development. By implementing this facial recognition system, candidates would need to identify their identity before entering exam centres, as it is to reducing cheating and impersonation. The system aims to verify candidates swiftly and accurately, improving the overall exam process. In conclusion, this project to develop a facial recognition system for exam centres is a step towards enhancing exam integrity and preventing identity fraud. Through advanced technology, the project aims to accurately identify candidates, reduce fraud, and provide insights into exam performance. It could have a big impact on education and lead to future advancements in exams and identity verification.